High Incidence of Bell's Palsy After Mastoidectomy: A Longitudinal Follow-up Study. Issue 10 (December 2017) - Choi, Hyo Geun; Sim, Songyong; Hong, Sung Kwang; Park, Su-kyoung; Lee, Hyo-Jeong; Chang, Jiwon
Abstract : Objective: The objective of this study was to compare the prevalence of Bell's palsy in participants who underwent mastoidectomy (to treat chronic otitis media) and nonmastoidectomy participants (control). Methods: Using the national cohort study from the Korean Health Insurance Review and Assessment Service, mastoidectomy patients (2, 045) and control participants (8, 180) were matched 1:4 for age, sex, income, and region of residence. The prevalence of Bell's palsy in both the groups was measured from 0 to 10 years postoperation. Results: In a sample of 1, 025, 340 Korean individuals, 7, 070 were diagnosed or treated with Bell's palsy between 2002 and 2013; the annual incidence of Bell's palsy was 0.057%. The overall prevalence of Bell's palsy was three times higher in the mastoidectomy group (1.27%) than control group (0.49%) ( p  < 0.001). The prevalence of Bell's palsy was different between the two groups in postoperative 0 year: 0.78% for the mastoidectomy group versus 0.01% for the control group ( p  < 0.001). Conclusion: Although we could not verify the laterality, the prevalence of Bell's palsy was increased in chronic otitis media patients treated with mastoidectomy patients compared with controls, especially within a year after surgery.